Pengaruh Stereotipe Dan Kemandirian Terhadap Konsep Diri Remaja Di SMK 5 Kota Bengkulu - Muzaro’ah, Muzaro’ah; Rahmat, Agung; Rismawati, Siti (DAWUH : Islamic Communication Journal, 2023)
This research aims to see the influence of stereotypes and independence on the self-concept of teenagers at SMKN 5 Bengkulu City. This research uses quantitative methods, with data collection techniques by distributing a 30-item questionnaire. The samples taken in this research were teenagers at SMKN 5 Bengkulu City. Data collection totaled 101 respondents. This research was analyzed using quantitative analysis using SPSS by testing Correlations Regression, Normality Test, Reliability Test, Hitosgram, and R Square. Based on this research, it shows that the influence of stereotypes and independence on self-concept at SMKN 5 Bengkulu City is in the weak category, namely 3.3%.